Efficiency of Cordia MYXA (Bumber) Fruit Powder added to Broiler Diets Exposed to Heat Stress on Productive and Physiological Performance - Nashwan Majeed Ali Al-Gburi, Mohammed Rasoul Mahdi Jasim (Pakistan Journal of Medical & Health Sciences, 2022)
As a scientific attempt to find food alternatives that contribute to alleviating the heat stress that birds are exposed to, this study resorted to showing the effect of using different levels of Bumber fruit powder to the diets of broilers exposed to heat stress, 240 one-day-old broilers of Ross 308 breed, bred in One of the fields belonging to broiler breeders in the district of Jableh, 65 km north of the center of Babil Governorate (Babylon city), Iraq. The birds were randomly distributed to four treatments, each treatment 60 birds and three replicates for each treatment (20 birds per replicate), the experiment transactions were divided into: Control treatment (C) without Any addition, the first treatment (B1) was added to its diet Bumber fruits powder at an amount of 2 g/kg of feed, the second treatment (B2) was added to its diet by Bumber fruits powder at an amount of 3 g/kg of fodder, and the third treatment (B3) was added to its diet by Bumber fruits powder at an amount of 4 g/kg of feed, during the six-week trial period, the productive characteristics of (body weight, weight gain, feed consumption, food conversion factor) were studied, which were studied weekly starting from the age of one day, in addition to the characteristics of blood plasma represented by (total glucose, cholesterol For total, total protein, liver enzymes (AST, ALT, ALP, HDL, LDL, VLDL) which were studied at the age of three and six weeks during the study period, the results of the current study indicated a significant improvement in the productive performance of diseased broilers to intermittent heat stress represented by weight gain. Body weight, feed consumption rate and food conversion factor, as well as the moral improvement in blood plasma characteristics represented in blood chemical characteristics and liver enzymes activity, in addition to a decrease in harmful fat levels in blood plasma. We conclude from the current study that adding Bumber fruit powder to broiler diets exposed to heat stress has significantly improved the productive and physiological performance of the bird, which may give the impression that adding this substance may add a significant difference in the general performance of the bird, which is positively reflected on the general health status of the bird.. Keywords: Broiler, Bumber, Heat Stress, Productive Performance, Physiological Performance